The Importance of NADPH Oxidases and Redox Signaling in Angiogenesis - Prieto-Bermejo, Rodrigo (Antioxidants (Basel), 2017)
Eukaryotic cells have to cope with the constant generation of reactive oxygen species (ROS). Although the excessive production of ROS might be deleterious for cell biology, there is a plethora of evidence showing that moderate levels of ROS are important for the control of cell signaling and gene expression. The family of the nicotinamide adenine dinucleotide phosphate oxidases (NADPH oxidases or Nox) has evolved to produce ROS in response to different signals; therefore, they fulfil a central role in the control of redox signaling. The role of NADPH oxidases in vascular physiology has been a field of intense study over the last two decades. In this review we will briefly analyze how ROS can regulate signaling and gene expression. We will address the implication of NADPH oxidases and redox signaling in angiogenesis, and finally, the therapeutic possibilities derived from this knowledge will be discussed.